Isolation and Identification of Organics-Degrading Bacteria From Gas-to-Liquid Process Water - Surkatti, Riham; Al Disi, Zulfa A.; El-Naas, Muftah H.; Zouari, Nabil; Van Loosdrecht, Mark C. M.; Onwusogh, Udeogu (Frontiers in Bioengineering and Biotechnology, 2021)
Gas to liquid (GTL) process generates considerable amounts of wastewater that are highly acidic and characterized by high COD, due to the presence of several organic pollutants, such as alcohols, ketones, aldehydes and fatty acids. The removal of organic pollutants is necessary to reduce the COD to an acceptable limit before discharging or reusing the treated water. Due to several advantages, biological treatment is often utilized as the main step in the GTL process water treatment plants. In order to have a successful bio-treatment process, it is necessary to choose effective and suitable bacterial strains that have the ability to degrade the organic pollutants in the GTL process water. In this work, bacterial strains were isolated from GTL process water, identified by 16S rRNA gene sequencing and then used in the biodegradation process. The detailed identification of the strains confirmed the presence of three organic degrading bacteria identified as Alcaligenes faecalis, Stenotrophomonas sp. and Ochrobactrum sp. Furthermore, biodegradation experiments were carried out and confirmed that pure as well as mixed culture consortium of the bacterial strains have the ability to reduce the organic pollutants in GTL process water. However, the growth rate and biodegradation efficiency depend on the type of strains. Indeed, the removal percentage and growth rate were enhanced after 7 days for all cultures and resulted in COD reduction up to 60%.